Relativistic electron acceleration by surface plasma waves excited with high intensity laser pulses - Zhu X. M. (HIGH POWER LASER SCIENCE AND ENGINEERING, 2020)
The process of high energy electron acceleration along the surface of grating targets (GTs) that were irradiated by a relativistic, high-contrast laser pulse at an intensity was studied. Our experimental results demonstrate that for a GT with a periodicity twice the laser wavelength, the surface electron flux is more intense for a laser incidence angle that is larger compared to the resonance angle predicted by the linear model. An electron beam with a peak charge of , for electrons with energies , was measured. Numerical simulations carried out with parameters similar to the experimental conditions also show an enhanced electron flux at higher incidence angles depending on the preplasma scale length. A theoretical model that includes ponderomotive effects with more realistic initial preplasma conditions suggests that the laser-driven intensity and preformed plasma scale length are important for the acceleration process. The predictions closely match the experimental and computational results.